Hunger and Public Action - Drèze, Jean (Oxford University Press, 1991)
This book analyses the role of public action in solving the problem of hunger in the modern world. The study is divided into four parts. The first, making extensive use of the concepts of entitlements and capabilities explores the interaction of nutritional, economic, social, and political elements and their influence on hunger and deprivation. The problem of famine prevention is the main focus of the second part, with special attention given to Africa and India. The third part is devoted to the issue of fighting chronic undernourishment and the lessons to be learnt from the policies of China, India, and some other countries. The last part draws together the main themes and concerns of the earlier chapters, and provides an integrated view of the role of public action in eliminating hunger. The study suggests that there is indeed some space for public action in solving the problem of hunger and deprivation. In the case of famine prevention, social security could provide early warning systems and employment provision plans. To fight endemic deprivation, the authors suggest, among other things, that basic health care, elementary education, and food programmes should be looked at.